Наукова робота студентів - Яковенко, Р. В.; Yakovenko, R. (Лисенко В. Ф., 2019)
Посібник містить методичні поради щодо організації та проведення наукової роботи студентів. Наведено загальні вимоги щодо оформлення результатів наукових досліджень, визначено принципи та етапи творчої взаємодії студентів з науковими керівниками. The guide includes advice on teaching and the organization of research work of students. An overall requirements for the presentation of results of research, the principles and steps of the creative interaction of students with academic leaders.
Scientific work of students
Keywords: науково-дослідна робота; студенти; дослідження; публікація; методологія; scientific research work; students; research; methodology